The Effect of Probability, Company Size and Capital Structure on the Value of Manufacturing Companies on the IDX for the 2021-2023 Period - Fitri Masyta Vidyani; Zeni Rusmawati; Tyasha Ayu Melynda Sari (P3I UMSurabaya, 2025)
This study aims to analyze the effect of profitability, company size, and capital structure on the value of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. Company value is measured using the Price to Book Value (PBV) ratio, while profitability is measured by Return On Equity (ROE), company size with the natural logarithm of total assets, and capital structure with the Debt to Eruity Ratio (DER). The research method used is quantitative with a descriptive approach. Data analysis was carried out using multiple linear regression with the help of SPSS software. The research sample consisted of 50 companies selected through the purposive sampling method, with a total observation of 150 data. The results of the study indicate that partially profitability does not have a significant effect on company value, company size does not have a significant effect on company value, and capital structure has a significant positive effect on company value. Simultaneously, profitability, company size, and capital structure have a significant effect on company value.